Method for producing anode for fluorine gas electrolytic synthesis
By using a carbon material anode substrate impregnated with potassium hexafluoro nickel (IV) acid in fluorogeneous electrolytic synthesis, a nickel fluoride coating is formed, which solves the problem of carbon electrode anode effect and improves electrolytic stability and The current density reduces the manufacturing cost of fluorine gas.
Patent Information
- Application Number
- CN202480002276.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-27
- Filing Date
- 2024-03-11
- Publication Date
- 2024-12-31
AI Technical Summary
During the electrolytic synthesis of fluorine gas, carbon electrodes are prone to anode effect, which leads to difficulty in contact with the electrode surface and decreases current flow, affecting electrolytic stability and efficiency.
By adopting a manufacturing method, by performing anodic polarization treatment in an electrolyte containing hydrogen fluoride and metal fluoride, using potassium hexafluoride nickel (IV) acid, an electric current flows between the anode and the cathode. A nickel fluoride coating is formed to inhibit the occurrence of anode effect.
It effectively suppresses the generation of anode effect, improves the continuous stability and current density of electrolysis, and reduces the cost of fluorine gas manufacturing.
Smart Images

Figure CN119234057A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing an anode for fluorine gas electrolytic synthesis. Background Art
[0002] Fluorine gas can be synthesized by electrolyzing an electrolyte containing hydrogen fluoride and metal fluoride. In the case of electrolytic synthesis of fluorine gas, KF·2HF (a mixed molten salt of hydrogen fluoride and potassium fluoride, the molar ratio of hydrogen fluoride to potassium fluoride in the mixed molten salt is hydrogen fluoride: potassium fluoride = 2:1) is generally used as the electrolyte, and a carbon electrode is used as the anode, and the electrolysis is performed at an electrolysis temperature of 80°C to 100°C.
[0003] However, when a carbon electrode is used as an anode, the phenomenon that the anode voltage rises and the flow of current decreases during electrolysis (hereinafter sometimes referred to as "anode effect") is likely to occur, so there is a problem that electrolysis may not be performed continuously and stably for a long time. The anode effect is a phenomenon that when a discharge reaction of fluorine ions (fluorine-containing ions) occurs on the surface of the carbon electrode, fluorinated graphite ((CF)n) with extremely low surface energy is formed on the surface of the carbon electrode, so that the electrolyte and the surface of the carbon electrode become difficult to contact, and the flow of current deteriorates.
[0004] Patent Document 1 discloses an electrode in which a metal fluoride is supported in the pores of porous carbon as a carbon electrode for suppressing the anode effect. Patent Document 2 discloses a technique for coating the surface of a carbon electrode with a film containing a nickel potassium fluoride compound in order to inhibit the formation of fluorinated graphite.
[0005] Prior art literature
[0006] Patent Document 1: Japanese Patent Gazette No. 3037464
[0007] Patent Document 2: Japanese Patent Gazette No. 5772102 Summary of the invention
[0008] When electrolysis of an electrolyte is performed using a carbon electrode as an anode, a technique for more fully suppressing the occurrence of the anode effect is desired.
[0009] An object of the present invention is to provide a method for producing an anode which is unlikely to produce an anode effect even when used when an electrolyte solution containing hydrogen fluoride and a metal fluoride is electrolyzed to electrolytically synthesize fluorine gas.
[0010] In order to solve the above-mentioned problems, one aspect of the present invention is as described in the following [1] to [8].
[0011] [1] A method for producing an anode for electrolytic synthesis of fluorine gas, the anode being usable when electrolyzing an electrolyte solution containing hydrogen fluoride and a metal fluoride to electrolytically synthesize fluorine gas, the method comprising an anode polarization treatment step,
[0012] In the anode polarization treatment step, an anode substrate having a carbon material is immersed as an anode, and a cathode is immersed in a mixed solution for anode manufacturing containing hydrogen fluoride, metal fluoride and potassium hexafluoronickel (IV) oxide, and an electric current is passed between the anode and the cathode to perform an anode polarization treatment on the anode substrate, thereby attaching nickel fluoride to the surface of the anode substrate.
[0013] [2] The method for producing an anode for fluorine gas electrolytic synthesis according to [1], wherein the concentration of the potassium hexafluoronickel(IV)ate in the mixed solution for producing the anode is 500 mass ppm or more and 5000 mass ppm or less.
[0014] [3] The method for producing an anode for fluorine gas electrolytic synthesis according to [1] or [2], wherein in the anode polarization treatment, the anode current density is 0.01 A / cm 2 Above and 0.8A / cm 2 The current per unit surface area of the anode substrate is 100 coulombs / cm 2 Above and 5000 Coulomb / cm 2 the following.
[0015] [4] The method for producing an anode for fluorine gas electrolytic synthesis according to any one of [1] to [3], wherein the nickel fluoride has nickel ions having a valence greater than 2.
[0016] [5] The method for producing an anode for fluorine gas electrolytic synthesis according to any one of [1] to [3], wherein the nickel fluoride is at least one of nickel trifluoride, nickel pentafluoride and nickel tetrafluoride.
[0017] [6] The method for producing an anode for fluorine gas electrolytic synthesis according to any one of [1] to [5], wherein the metal fluoride is at least one of potassium fluoride and cesium fluoride.
[0018] [7] The method for producing an anode for fluorine gas electrolytic synthesis according to any one of [1] to [6], wherein the ratio of the molar amount of the hydrogen fluoride contained in the mixed solution for producing the anode to the molar amount of the metal fluoride is 1.6 or more and 3.2 or less.
[0019] [8] The method for producing an anode for fluorine gas electrolytic synthesis according to any one of [1] to [7], wherein the cathode is an electrode formed of at least one of iron, nickel, copper and a copper-nickel alloy.
[0020] According to the present invention, it is possible to produce an anode that is unlikely to produce an anode effect even when used when fluorine gas is electrolyzed by electrolyzing an electrolyte solution containing hydrogen fluoride and a metal fluoride. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a diagram for explaining an example of an electrolytic cell in which the method for producing an anode for fluorine gas electrolytic synthesis according to the present embodiment can be implemented.
[0022] Figure 2 This is a diagram showing a cyclic voltammogram obtained by cyclic voltammetry. DETAILED DESCRIPTION
[0023] Hereinafter, an embodiment of the present invention will be described. Furthermore, this embodiment represents an example of the present invention, and the present invention is not limited to this embodiment. In addition, various changes or improvements can be applied to this embodiment, and such a changed or improved method is also included in the present invention.
[0024] The method for manufacturing an anode for electrolytic synthesis of fluorine gas of the present embodiment is a method for manufacturing an anode that can be used when electrolytic synthesis of fluorine gas (F2) is performed by electrolyzing an electrolyte solution containing hydrogen fluoride (HF) and a metal fluoride, and the method comprises an anode polarization treatment step. The anode polarization treatment step is a step of immersing an anode substrate having a carbon material as an anode and a cathode in a mixed solution for manufacturing an anode containing hydrogen fluoride, a metal fluoride and potassium hexafluoronickel (IV) acid (K2NiF6), passing a current between the anode (anode substrate) and the cathode to perform an anode polarization treatment of the anode substrate, and attaching nickel fluoride to the surface of the anode substrate.
[0025] The anode manufactured by the manufacturing method of the anode for fluorine gas electrolytic synthesis of the present embodiment (hereinafter sometimes referred to as "the anode for fluorine gas electrolytic synthesis of the present embodiment") is anode polarized in the anode polarization treatment, and nickel fluoride is attached to the surface of the anode substrate (for example, a nickel fluoride film is formed on the surface of the anode substrate). Therefore, the anode for fluorine gas electrolytic synthesis of the present embodiment is not likely to produce an anode effect even when it is used when an electrolyte containing hydrogen fluoride and a metal fluoride is electrolyzed to electrolyze fluorine gas.
[0026] For example, when an electrolyte solution containing hydrogen fluoride and metal fluoride but not containing potassium hexafluoronickel (IV) oxide (e.g., KF·2HF) is electrolyzed to electrolyze fluorine gas, if the anode for fluorine gas electrolysis synthesis of the present embodiment is used, an anode current density of 0.01 A / cm 2 Above and 0.8A / cm 2The electrolysis in which the anode effect is suppressed is as follows. As a result, the frequency of interruption and stop of the operation of electrolytic synthesis of fluorine gas can be reduced, and electrolysis can be performed at a high current density, thereby reducing the production cost of fluorine gas.
[0027] Here, the anode effect is explained. When a carbon anode is subjected to anodic polarization in an electrolyte containing hydrogen fluoride and a metal fluoride, fluoride ions (hereinafter sometimes referred to as "HF2 - ") to generate fluorine atoms. The generated fluorine atoms couple to generate fluorine gas, but sometimes a part of the fluorine atoms are combined with the carbon of the carbon anode to form a hydrophobic fluorinated graphite film called (CF)n film on the surface of the carbon anode. As a result, it becomes difficult for the electrolyte to contact the surface of the carbon anode during electrolysis, so it is difficult for the fluorine ion discharge reaction to occur on the surface of the carbon anode, and the true current density increases, so the anode voltage increases and the flow of current decreases. This is the mechanism of the anode effect.
[0028] Patent Document 2 discloses a technique for coating the surface of a carbon electrode with a film other than a (CF)n film. That is, the following technique: an electrode having a structure in which a portion of the surface of a carbon substrate is coated with a conductive diamond layer and the other portion is not coated with a conductive diamond layer is subjected to a coating treatment with a film containing a nickel potassium fluoride compound, so that only the surface not coated with the conductive diamond layer is coated with the film containing a nickel potassium fluoride compound.
[0029] Since the surface of the carbon substrate is coated with a conductive diamond layer and a film containing a nickel potassium fluoride compound, it becomes difficult to form a (CF)n film on the surface. Examples of the nickel potassium fluoride compound include potassium hexafluoronickel (IV) oxide (K2NiF6).
[0030] Patent Document 2 describes the conditions for forming a film containing a nickel potassium fluoride compound, wherein the nickel ion concentration in the electrolyte is set to 10 ppm to 5%, preferably 30 ppm to 1000 ppm, by adding nickel fluoride to the electrolyte or dissolving nickel from the material of the electrolytic cell. In addition, regarding the electrolysis conditions of the electrolyte, the current density is 0.001 A / cm 2 Above and 0.05A / cm 2 Hereinafter, the electrolysis time is 0.1 hours to 10 hours.
[0031] Patent Document 2 states that if the current density is higher than 0.05 A / cm 2 , a fluorinated graphite layer is easily formed before the film containing the nickel potassium fluoride compound is formed, so it is not preferred. In addition, it is recorded that if the electrolysis time is longer than 10 hours, power consumption and productivity will decrease, so it is not preferred.
[0032] Therefore, as a method for making nickel ions coexist in the electrolyte, a method of adding nickel fluoride (NiF2, molecular weight 96.7g / mol) to the electrolyte was tried. 100g of KF·2HF liquid was added to a sealed container made of Teflon (registered trademark) stored in a thermostatic bath and maintained at 90°C, and 0.165g of nickel fluoride powder was added to the KF·2HF liquid in such a way that the concentration of nickel (atomic weight 58.7g / mol) in the KF·2HF liquid became 1000 mass ppm. Then, the liquid in the sealed container was stirred from time to time while being placed at 90°C for 36 hours. Since the dissolved residual nickel fluoride powder was confirmed at the bottom of the sealed container after placement, the nickel concentration in the KF·2HF liquid was measured by inductively coupled plasma emission spectrometry (ICP emission spectrometry) after removing the dissolved residual nickel fluoride powder, and the result was 164 mass ppm.
[0033] In addition, Patent Document 2 describes a method for dissolving nickel from the material of an electrolytic cell as a method for making nickel ions coexist in an electrolyte. If the material of the electrolytic cell is in a state of a potential higher than the dissolution potential of nickel (about 0.2 to 0.3 V vs. SEP) (a potential that is large in the positive direction), the nickel forming the electrolytic cell becomes ions and dissolves in the electrolyte.
[0034] In order to make nickel dissolve easily, the nickel forming the electrolytic cell is used as the anode, and the KF·2HF electrolyte at 85°C in the electrolytic cell is electrolyzed with a constant current. The mass of the nickel anode during electrolysis is measured regularly to measure the reduction in nickel. The electrolysis is continued until the reduction in nickel becomes an amount at which the nickel concentration in the KF·2HF electrolyte reaches 1000 mass ppm due to the dissolution of nickel. Since sludge-like deposits are confirmed at the bottom of the electrolytic cell, the nickel concentration in the KF·2HF electrolyte is measured by ICP emission spectrometry after removing the sludge-like deposits, and the result is 282 mass ppm.
[0035] Thus, it can be seen that as methods for making nickel ions coexist in the electrolyte, there are a method of adding nickel fluoride to the electrolyte and a method of dissolving nickel from the material of the electrolytic cell, but in these methods, the limit of the concentration of nickel dissolved in the electrolyte is about 200 to 300 mass ppm.
[0036] In contrast, potassium hexafluoronickel (IV) acid can dissolve more than 10% by mass in anhydrous hydrogen fluoride. Although it varies slightly depending on the temperature, the solubility of potassium hexafluoronickel (IV) acid in KF·2HF is about 0.5% by mass, and the concentration of dissolved nickel is about 1000 ppm by mass. Therefore, compared with the method described in Patent Document 2, more nickel electrolyte (divalent, trivalent, tetravalent nickel ions, etc.) can be dissolved in the KF·2HF electrolyte.
[0037] By the method of adding nickel fluoride to the electrolyte recorded in patent documentation 2, nickel fluoride is dissolved in KF·2HF liquid until 160 mass ppm close to saturated solubility, critical current density is measured, and it is known that the effect of suppressing the anode effect is poor. Details are described later in comparative example 1. Moreover, critical current density is the current density before the electrolysis voltage rises sharply. Because the phenomenon that the electrolysis voltage rises sharply is equivalent to the anode effect, it can be interpreted as that the critical current density is the electrode state that is more difficult to cause the anode effect with a larger value.
[0038] Next, the properties of the dissolved nickel electrolyte are described. Patent Document 2 states that "nickel ions are made to coexist in the molten salt, and the nickel ions form high-valent metal ions...", which can be interpreted as nickel dissolving in the electrolyte as divalent nickel ions.
[0039] In the technology disclosed in Patent Document 2, if the mechanism of potassium hexafluoronickel (IV) oxide coating the electrode is considered, it is believed that the divalent nickel ion (NiF4 2- ) diffuses on the surface of the electrode and reacts with fluorine gas or fluorine atoms generated on the surface of the electrode, and the divalent nickel ions are oxidized to tetravalent nickel ions (NiF6 2- ), and diffuses again on the surface of the electrode. It can be explained that the potassium ions present near the electrode combine with the tetravalent nickel ions and precipitate on the surface of the electrode, thereby coating the potassium hexafluoronickel (IV) oxide.
[0040] It can be easily predicted that since the amount of divalent nickel ions dissolved in the KF·2HF electrolyte is about 200 to 300 mass ppm, the amount of tetravalent nickel ions generated by the reaction with fluorine gas or fluorine atoms is very small. Therefore, it is believed that according to the technology disclosed in Patent Document 2, the formation of potassium hexafluoronickel (IV) acid film will hardly occur.
[0041] In addition, in other mechanisms, the possibility that nickel fluoride (NiF2) solid is formed by the discharge reaction of divalent nickel ions on the carbon surface, and the nickel fluoride on the carbon surface reacts with the generated fluorine gas to form a high-valent nickel fluoride compound is also considered. However, in general, it is expected that the reaction of nickel fluoride and fluorine gas to form nickel tetrafluoride (NiF4) requires a high reaction temperature of 250 to 450°C, so in the electrode reaction, the nickel fluoride on the carbon electrode hardly reacts with fluorine gas.
[0042] Regardless of the reaction pathway, in order for the dissolved divalent nickel ions to become high-valent, they need to interact with the fluorine gas generated in the electrode reaction. Unless fluorine gas is generated on the electrode, high-valent nickel ions cannot be generated. The generation of fluorine gas on the surface of the electrode means that a (CF)n film is also formed.
[0043] In this embodiment, the properties of the nickel electrolyte dissolved in the mixed solution for anode manufacturing are different from those of the technology disclosed in Patent Document 2, and therefore the effect on the surface of the carbon electrode is also different. In the method for manufacturing an anode for fluorine gas electrolytic synthesis of this embodiment, an anodic polarization treatment of the anode substrate is performed in a mixed solution for anode manufacturing in which free nickel hexafluoride (IV) ions are present, so that it is not related to the generation of fluorine gas based on the electrode reaction, and the nickel hexafluoride (IV) ions directly react with the surface of the anode substrate. Therefore, the film formed on the carbon surface shows completely different properties from the technology disclosed in Patent Document 2.
[0044] In order to make free nickel hexafluoride (IV) ions present in the mixed solution for anode manufacturing, it is preferred that the amount of impurities that are easily oxidized in the mixed solution for anode manufacturing is small. As impurities that are easily oxidized, water, sulfuric acid derived from raw materials, silicon compounds, etc. can be cited. For example, if water is present in the mixed solution for anode manufacturing, the nickel hexafluoride (IV) ions oxidize the water, so the nickel of the nickel hexafluoride (IV) ions is reduced to a low-valent state, and it is difficult to embody the effect of the present invention.
[0045] In the method for manufacturing an anode for fluorine gas electrolytic synthesis of the present embodiment, potassium hexafluoronickel (IV) acid is contained in the mixed solution for manufacturing the anode, but a metal fluoride complex salt capable of freeing hexafluoronickel (IV) ions may be used instead of potassium hexafluoronickel (IV) acid. Examples of such metal fluoride complex salts include cesium hexafluoronickel (IV) acid and rubidium hexafluoronickel (IV) acid.
[0046] When potassium hexafluoronickel (IV) acid, which is a red crystalline powder, is added to a transparent KF·2HF liquid and dissolved, if water is present in the KF·2HF liquid, potassium hexafluoronickel (IV) acid reacts with water, so that the red color of potassium hexafluoronickel (IV) acid disappears and the mixed solution for anode manufacturing displays a white turbid color. However, if free hexafluoronickel (IV) ions are present in the mixed solution for anode manufacturing, the mixed solution for anode manufacturing changes from light pink to dark red as the concentration of hexafluoronickel (IV) ions increases. If there are no free hexafluoronickel (IV) ions in the mixed solution for anode manufacturing, it is difficult to demonstrate the effect of the present invention.
[0047] The method for manufacturing the anode for electrolytic synthesis of fluorine gas of this embodiment can be implemented, for example, using an electrolytic cell. An example of an electrolytic cell is an electrolytic cell used when electrolyzing an electrolyte solution containing hydrogen fluoride and a metal fluoride to electrolytically synthesize fluorine gas. The details are described in the examples. For example, Figure 1 The electrolytic cell made of Teflon shown is used to produce the anode for electrolytic synthesis of fluorine gas according to the present embodiment.
[0048] for Figure 1 The structure of the Teflon electrolytic cell is briefly described. Figure 1In the electrolytic cell, the main body 11 containing the anode manufacturing mixed solution 10 is made of Teflon. In addition, the cover 12 of the main body 11 is made of a transparent acrylic plate, and the color of the anode manufacturing mixed solution 10 in the main body 11 can be confirmed. A Teflon partition 13 is provided inside the electrolytic cell, and the gas phase inside the electrolytic cell is divided into an anode side gas phase and a cathode side gas phase by the partition 13.
[0049] Although Figure 1 Although not shown, an inert gas supply pipe for supplying an inert gas to the inside of the electrolytic cell is connected to the electrolytic cell so that the gas phase inside the electrolytic cell can be diluted with an inert gas such as nitrogen. In addition, a hydrogen fluoride supply pipe 31 for supplying hydrogen fluoride to the mixed solution 10 for anode manufacturing in the main body 11 is connected to the electrolytic cell. Furthermore, a fluorine gas extraction pipe 33 and a hydrogen gas extraction pipe 34 for extracting fluorine gas and hydrogen generated by the anode 21 and the cathode 22 from the electrolytic cell are respectively connected to the electrolytic cell.
[0050] The electrolytic cell is provided with an external heater (not shown) that can heat the anode manufacturing mixed solution 10 in the main body 11 to a temperature of, for example, 85° C. The electrolytic cell is provided with a thermometer 32 such as a thermocouple that can measure the temperature of the anode manufacturing mixed solution 10 in the main body 11. The electrolytic cell is provided with a stirring device (not shown) that can stir the anode manufacturing mixed solution 10 in the main body 11.
[0051] The mixed solution 10 for manufacturing the anode is a mixed solution containing hydrogen fluoride, metal fluoride and potassium hexafluoronickel (IV) acid, for example, KF·2HF in which potassium hexafluoronickel (IV) acid is dissolved. The electrolytic cell includes an anode 21 and a cathode 22, and both the anode 21 and the cathode 22 are immersed in the mixed solution 10 for manufacturing the anode. The anode 21 is an anode substrate having a carbon material, for example, a plate made of amorphous carbon. The cathode 22 is, for example, a metal plate formed of a metal such as nickel. The electrolytic cell is set in a drying box to suppress the water in the atmosphere from dissolving into the mixed solution 10 for manufacturing the anode in the main body 11.
[0052] [Dehydrated electrolyte 1 prepared by performing dehydration electrolysis 1]
[0053] use Figure 1 The electrolytic cell was used to perform dehydration electrolysis of an electrolyte solution which was a mixture of hydrogen fluoride and potassium fluoride. The anode current density was 0.3 A / cm 2 The electrolysis time was 2 hours. In addition, a conductive diamond electrode coated with conductive diamond was used as the anode. The shape of the anode was a square with a length of 1 cm and a width of 1 cm.
[0054] Since conductive diamond has sp3 orbital carbon bonds, the (CF)n film formed by the reaction of sp2 orbital carbon and fluorine gas will not form on the surface of the conductive diamond electrode. Therefore, the conductive diamond electrode is an electrode that does not produce an anode effect. Therefore, if a conductive diamond electrode is used, dehydration electrolysis can be performed without causing an anode effect even in the presence of water in the electrolyte.
[0055] The gas generated from the anode was diluted with nitrogen, the fluorine gas was absorbed and removed by the potassium iodide aqueous solution trap, and the oxygen concentration in the gas discharged from the potassium iodide aqueous solution trap was measured by gas chromatography. As a result, no oxygen was detected, so it was determined that the dehydration electrolysis was completed.
[0056] Since hydrogen fluoride is consumed by electrolysis, hydrogen fluoride is intermittently supplied to the electrolyte during dehydration electrolysis so that the concentration of hydrogen fluoride in the electrolyte is in the range of 40 mass % to 43 mass %. Such an operation is called dehydration electrolysis 1, and the electrolyte prepared by performing dehydration electrolysis 1 is called dehydrated electrolyte 1.
[0057] [Potassium hexafluoronickel (IV) oxide added electrode 1]
[0058] Crystal powder of potassium hexafluoronickel (IV)ate was added to the dehydrated electrolyte 1 so that the concentration of potassium hexafluoronickel (IV)ate in the dehydrated electrolyte 1 was 0.1 mass %. The concentration of nickel in the dehydrated electrolyte 1 was 210 mass ppm. When potassium hexafluoronickel (IV)ate was added, a small amount of potassium hexafluoronickel (IV)ate reacted, but the crystal powder of potassium hexafluoronickel (IV)ate was completely dissolved, and the dehydrated electrolyte 1 was light red.
[0059] A portion of the dehydrated electrolyte 1 (corresponding to the mixed solution for anode production) in which potassium hexafluoronickel (IV) oxide was dissolved was prepared, and the nickel concentration in the dehydrated electrolyte 1 was measured by ICP emission spectrometry. As a result, it was confirmed that nickel in an amount equivalent to the added amount was dissolved.
[0060] A 1 cm long and 1 cm wide square carbon electrode (equivalent to the anode substrate) was immersed as an anode in the dehydrated electrolyte 1 in which potassium hexafluoronickel (IV) oxide was dissolved, and a metal cathode was immersed. Then, a current of 0.1 A was passed between the anode and the cathode for 1 hour to perform a surface treatment of the carbon electrode (equivalent to an anodic polarization treatment).
[0061] The amount of electricity per unit surface area of the carbon electrode during the surface treatment was 360 coulombs / cm 2. In addition, the carbon electrode is a new product (a product that has not been used for electrolysis) of grade ABR manufactured by SGL Carbon. The carbon electrode subjected to such surface treatment is referred to as potassium hexafluoronickel (IV) acid added electrode 1. In addition, the "carbon electrode" below is a new product (a product that has not been used for electrolysis) of grade ABR manufactured by SGL Carbon unless otherwise specified.
[0062] [Patent Document 2 Additional Test Electrode 1]
[0063] A rectangular nickel plate with a length of 2 cm and a width of 3 cm was immersed as an anode, and a metal cathode was immersed in the dehydrated electrolyte 1. Then, a current of 0.6 A was passed between the anode and the cathode for 16 hours to perform electrolysis, so that nickel was dissolved from the nickel plate into the dehydrated electrolyte 1. The dehydrated electrolyte 1 after electrolysis was pale yellow-green.
[0064] The nickel concentration in the dehydrated electrolyte 1 from which nickel was dissolved was calculated to be 1000 mass ppm based on the mass reduction of the nickel plate. However, a precipitate was produced in the dehydrated electrolyte 1 from which nickel was dissolved. The nickel concentration in the dehydrated electrolyte 1 not containing the precipitate was measured by ICP emission spectrometry, and the result was 220 mass ppm.
[0065] A square carbon electrode of 1 cm in length and 1 cm in width was immersed as an anode in the dehydrated electrolyte 1 from which nickel was dissolved, and a metal cathode was immersed. Then, electrolysis was performed by passing a current of 25 mA between the anode and the cathode for 3 hours. By this electrolysis, a nickel potassium fluoride film was formed on the surface of the carbon electrode. The amount of current per unit surface area of the carbon electrode in this electrolysis was 270 coulombs / cm 2 In addition, the current density in this electrolysis is 0.0025A / cm 2 .
[0066] The carbon electrode on which the nickel potassium fluoride film is formed in this way is the electrode described in Patent Document 2, and thus this carbon electrode is referred to as Patent Document 2 Additional Test Electrode 1.
[0067] [Patent Document 2 Additional Test Electrode 2]
[0068] A rectangular nickel plate with a length of 2 cm and a width of 3 cm was immersed as an anode, and a metal cathode was immersed in the dehydrated electrolyte 1. Then, electrolysis was performed by passing a current of 1 A between the anode and the cathode for 26 hours, so that nickel was dissolved from the nickel plate into the dehydrated electrolyte 1. The dehydrated electrolyte 1 after electrolysis showed a light yellow-green color (the green color was slightly darker than the color of the dehydrated electrolyte 1 in the case of adding the test electrode 1 in Patent Document 2).
[0069] The nickel concentration in the dehydrated electrolyte 1 from which nickel was dissolved was calculated to be 2700 mass ppm based on the mass reduction of the nickel plate. However, a precipitate was produced in the dehydrated electrolyte 1 from which nickel was dissolved. The nickel concentration in the dehydrated electrolyte 1 not containing the precipitate was measured by ICP emission spectrometry, and the result was 280 mass ppm.
[0070] A square carbon electrode 1 cm long and 1 cm wide was immersed as an anode in the dehydrated electrolyte 1 from which nickel was dissolved, and a metal cathode was immersed. Then, electrolysis was performed by passing a current of 25 mA between the anode and the cathode for 3 hours. By this electrolysis, a nickel potassium fluoride film was formed on the surface of the carbon electrode. The amount of current per unit surface area of the carbon electrode in this electrolysis was 270 coulombs / cm 2 In addition, the current density in this electrolysis is 0.0025A / cm 2 .
[0071] The carbon electrode on which the nickel potassium fluoride film is formed in this way is the electrode described in Patent Document 2, and thus this carbon electrode is referred to as Patent Document 2 Additional Test Electrode 2.
[0072] [Determination of blank critical current density]
[0073] A square carbon electrode with a length of 1 cm and a width of 1 cm was immersed as an anode in the dehydrated electrolyte 1, and a metal cathode was immersed, and the critical current density was measured. Hereinafter, the critical current density measured by this method is referred to as blank critical current density, which means the critical current density in a state where no treatment is performed on the electrode.
[0074] The determination method of critical current density is as follows. Between anode and cathode, initially with the direct current of 25mA for 15 minutes, thereafter with the direct current of 50mA for 15 minutes. And then, every energization makes electric current rise 25mA for 15 minutes, the current density before the electrolysis voltage is sharply raised is as critical current density.
[0075] Since the phenomenon of the rapid rise of the electrolysis voltage is equivalent to the anode effect, it can be judged that the greater the value of the critical current density, the more difficult it is to cause the electrode state of the anode effect. The critical current density shown below is the value obtained by this determination method unless otherwise specified. After measuring the critical current density, the anode is taken out from the electrolytic cell.
[0076] The critical current density (blank critical current density) was measured for the dehydrated electrolyte 1 containing no nickel ions by the above-mentioned measurement method. The carbon electrode used in this measurement was a carbon electrode that was not used for the measurement of critical current density and electrolysis. The carbon electrode was replaced with a new one 6 times, and the critical current density was measured 6 times. The average value of the measured value was 0.29 A / cm 2 , the maximum value is 0.35A / cm2 , the minimum value is 0.225A / cm 2 .
[0077] [Determination of critical current density of treatment electrode]
[0078] A method of directly measuring the critical current density of the anode manufactured by the method for manufacturing an anode for fluorine gas electrolytic synthesis of the present embodiment without removing it from the mixed solution for manufacturing the anode used in the manufacturing is referred to as critical current density measurement method A.
[0079] In addition, the anode manufactured by the manufacturing method of the anode for fluorine gas electrolytic synthesis of this embodiment is taken out from the mixed solution for anode manufacturing used during manufacturing, and immersed in a dehydrated electrolyte 1 to which no nickel electrolyte is added or in a dehydrated electrolyte 1 in the absence of nickel electrolyte. The method of measuring the critical current density is called critical current density measurement method B.
[0080] The critical current density of the potassium hexafluoronickel(IV)ate-added electrode 1 was measured by critical current density measurement method A. As a result, the critical current density was 0.575 A / cm 2 .
[0081] Furthermore, the production of the potassium hexafluoronickel (IV) oxide-added electrode 1 was carried out twice, and the critical current density of each electrode was measured by the critical current density measurement method A. As a result, the critical current density was 0.575 A / cm 2 and 0.675A / cm 2 .
[0082] As described above, the critical current density of the electrode 1 containing potassium hexafluoronickel(IV)ate is 2 to 3 times higher than the blank critical current density.
[0083] Next, the critical current density of the potassium hexafluoronickel (IV) acid added electrode 1 is measured by the critical current density measurement method B. That is, the potassium hexafluoronickel (IV) acid added electrode 1 is taken out from the anode manufacturing mixed solution used when manufacturing the potassium hexafluoronickel (IV) acid added electrode 1. Then, in another electrolytic cell having the same structure as the electrolytic cell used when manufacturing the potassium hexafluoronickel (IV) acid added electrode 1, a dehydrated electrolyte 1 is prepared, and the taken out potassium hexafluoronickel (IV) acid added electrode 1 is installed in the other electrolytic cell to measure the critical current density.
[0084] The critical current density was determined to be 0.550 A / cm 2 Therefore, it can be said that the potassium hexafluoronickel (IV) oxide added electrode 1 maintains the surface modified state.
[0085] The above series of electrode replacement operations were performed in a glove box under a nitrogen atmosphere free of water.
[0086] Next, the critical current density of the additional test electrode 1 of Patent Document 2 and the additional test electrode 2 of Patent Document 2 was measured by critical current density measurement method A. The critical current density of the additional test electrode 1 of Patent Document 2 was 0.300 A / cm 2 The color of the electrolyte was pale yellow-green and did not change, and it could not be said that nickel hexafluoride (IV) ions were present.
[0087] Patent Document 2 Additional Test The critical current density of electrode 2 is 0.350 A / cm 2 The color of the electrolyte was pale yellow-green and did not change, and it could not be said that nickel hexafluoride (IV) ions were present. The critical current density of the additional test electrode 1 of Patent Document 2 and the additional test electrode 2 of Patent Document 2 was slightly higher than the average value of the blank critical current density, but did not exceed the maximum value of the blank critical current density.
[0088] As described above, it is known that the anode produced by the method for producing an anode for fluorine gas electrolytic synthesis of this embodiment is very unlikely to cause the anode effect. The mechanism of suppressing the anode effect is not yet fully understood, but it is presumed to be related to the presence of a fluorinating agent on the surface of the electrode.
[0089] Hereinafter, the method for producing the anode for fluorine gas electrolytic synthesis according to the present embodiment will be described in more detail.
[0090] As an example of an apparatus for implementing the method for manufacturing an anode for electrolytic synthesis of fluorine gas of this embodiment, an electrolytic cell used in electrolytic synthesis of fluorine gas can be cited. There is no particular limitation on the form of the electrolytic cell, and any electrolytic cell can be used as long as it is an electrolytic cell that can electrolyze an electrolyte containing hydrogen fluoride and a metal fluoride to produce fluorine gas.
[0091] Generally, the interior of the electrolytic cell is divided into an anode chamber where an anode is arranged and a cathode chamber where a cathode is arranged by a partition member such as a partition wall so that fluorine gas generated at the anode and hydrogen gas generated at the cathode are not mixed.
[0092] The interior of the electrolytic cell is divided into an anode chamber equipped with an anode and a cathode chamber equipped with a cathode, but the anode manufacturing mixed solution contained in the anode chamber and the anode manufacturing mixed solution contained in the cathode chamber are not isolated. Most of them are structures in which the anode manufacturing mixed solutions contained in the two electrode chambers can mix freely.
[0093] When the interior of the electrolytic cell is structured so that the anode manufacturing mixed solution contained in the two electrode chambers can be freely mixed, potassium hexafluoronickel (IV) oxide may be contained in either the anode manufacturing mixed solution contained in the anode chamber or the cathode chamber.
[0094] As the anode, for example, a carbonaceous electrode formed of a carbon material such as diamond, diamond-like carbon, amorphous carbon, graphite, glassy carbon, etc. can be used. As the cathode, for example, a metal electrode formed of a metal such as iron (Fe), nickel (Ni), copper (Cu), copper-nickel alloy (for example, MONEL (trademark)) can be used.
[0095] The mixed solution for manufacturing the anode contains hydrogen fluoride, metal fluoride and potassium hexafluoronickel (IV) acid. The type of metal fluoride is not particularly limited, but alkali metal fluoride is preferred, and at least one of potassium fluoride (KF) and cesium fluoride (CsF) is more preferred. The metal fluoride may be used alone or in combination of two or more. That is, potassium fluoride and cesium fluoride may also be used in combination as the metal fluoride.
[0096] The ratio of the molar amount of hydrogen fluoride contained in the anode manufacturing mixed solution to the molar amount of the metal fluoride ([molar amount of hydrogen fluoride] / [molar amount of metal fluoride]) is preferably 1.6 to 3.2, more preferably 1.9 to 3.0.
[0097] As a mixed solution for manufacturing the anode, for example, a mixed solution in which potassium hexafluoronickel (IV) acid is dissolved in a mixed molten salt of hydrogen fluoride and potassium fluoride can be used. The molar ratio of hydrogen fluoride to potassium fluoride in the mixed molten salt of hydrogen fluoride and potassium fluoride can be, for example, hydrogen fluoride: potassium fluoride = 1.5 to 2.5: 1. KF·2HF at hydrogen fluoride: potassium fluoride = 2: 1 is a representative mixed molten salt, and the melting point of the mixed molten salt is about 72°C.
[0098] In addition, as an example of a mixed solution for manufacturing an anode, a mixed solution in which potassium hexafluoronickel (IV) acid is dissolved in a mixed molten salt of hydrogen fluoride and cesium fluoride can also be used. The molar ratio of hydrogen fluoride to cesium fluoride in the mixed molten salt of hydrogen fluoride and cesium fluoride can be, for example, hydrogen fluoride: cesium fluoride = 1.8: 1 to 3.1: 1. CsF·2.4HF when hydrogen fluoride: cesium fluoride = 2.4: 1 is a representative mixed molten salt, and the melting point of the mixed molten salt is about 16°C.
[0099] Since the mixed solution for producing the anode is corrosive, the inner surface of the electrolytic cell and other parts that come into contact with the mixed solution for producing the anode are preferably formed of a metal such as iron, nickel, or MONEL (trademark).
[0100] Since hydrogen fluoride in the mixed solution for anode manufacturing is consumed by electrolysis during anode manufacturing, it is preferred to supply hydrogen fluoride to the mixed solution for anode manufacturing continuously or intermittently during electrolysis during anode manufacturing. Hydrogen fluoride may be supplied to the mixed solution for anode manufacturing on the cathode chamber side of the electrolytic cell or to the mixed solution for anode manufacturing on the anode chamber side.
[0101] Regarding the concentration of hydrogen fluoride in the mixed solution for manufacturing the anode, if the concentration of hydrogen fluoride when the mixed molten salt used in the mixed solution for manufacturing the anode is KF·2HF (hydrogen fluoride concentration: 40.4 mass%) or CsF·2.4HF (hydrogen fluoride concentration: 24.0 mass%) is used as the reference concentration, it is preferably controlled to fluctuate within a range of not less than -5 mass% and not more than +5 mass% of the reference concentration, more preferably controlled to fluctuate within a range of not less than -2.5 mass% and not more than +2.5 mass% of the reference concentration, and further preferably controlled to fluctuate within a range of not less than -1.5 mass% and not more than +1.5 mass% of the reference concentration.
[0102] The mixed solution for manufacturing the anode can be obtained by mixing hydrogen fluoride, metal fluoride and potassium hexafluoronickel (IV) acid (K2NiF6). Potassium hexafluoronickel (IV) acid can be a commercial product or a prepared product. Potassium hexafluoronickel (IV) acid can be prepared by mixing potassium fluoride and nickel fluoride (NiF2) in a molar ratio of 2:1 and treating at a temperature of 250°C or more and 450°C or less in a fluorine gas atmosphere.
[0103] Potassium hexafluoronickel (IV) acid is a solid that shows oxidizability, so it reacts with water to change into a potassium fluoride salt of trivalent nickel (K2NiF5) or a potassium fluoride salt of divalent nickel (K2NiF4). Regarding the solubility in the mixed solution for anode manufacturing, potassium pentafluoronickel (III) acid (K2NiF5) and potassium tetrafluoronickel (II) acid (K2NiF4) are lower than potassium hexafluoronickel (IV) acid. Therefore, it is preferred to use potassium hexafluoronickel (IV) acid with a low water content. The water content contained in potassium hexafluoronickel (IV) acid is preferably 0.5% by mass or less, and more preferably 0.3% by mass or less.
[0104] The method for making the mixed solution for manufacturing the anode contain potassium hexafluoronickel (IV) acid is not particularly limited. The mixed solution for manufacturing the anode can be prepared by mixing a metal fluoride with liquid hydrogen fluoride in which potassium hexafluoronickel (IV) acid is dissolved, or by mixing solid potassium hexafluoronickel (IV) acid with a mixture of hydrogen fluoride and metal fluoride. In addition, potassium hexafluoronickel (IV) acid can be added in a predetermined amount at one time or in divided amounts.
[0105] The concentration of potassium hexafluoronickel (IV) oxide in the mixed solution for producing the anode is preferably 500 mass ppm or more and 5000 mass ppm or less, and more preferably 1000 mass ppm or more and 4000 mass ppm or less.
[0106] In the mixed solution for manufacturing the anode, it is okay to contain potassium hexafluoronickel (IV) acid in an amount exceeding the saturated solubility. If potassium hexafluoronickel (IV) acid is contained in an amount exceeding the saturated solubility, the undissolved solid matter of potassium hexafluoronickel (IV) acid is accumulated at the bottom of the electrolytic cell. If the manufacturing method of the anode for fluorine gas electrolytic synthesis of the present embodiment is implemented, the nickel electrolyte in the mixed solution for manufacturing the anode becomes nickel fluoride attached to the surface of the anode substrate, so the concentration of the nickel electrolyte in the mixed solution for manufacturing the anode decreases. If the mixed solution for manufacturing the anode contains potassium hexafluoronickel (IV) acid in an amount exceeding the saturated solubility, as the concentration of the nickel electrolyte decreases, the undissolved solid matter of potassium hexafluoronickel (IV) acid dissolves, thereby maintaining the state of saturated solubility.
[0107] In the method for manufacturing an anode for fluorine gas electrolysis synthesis of the present embodiment, a current is passed between the anode (anode substrate) and the cathode to perform an anodic polarization treatment on the anode substrate so that nickel fluoride adheres to the surface of the anode substrate. In the anodic polarization treatment, the anode current density is preferably 0.01 A / cm 2 Above and 0.8A / cm 2 The amount of current per unit surface area of the anode substrate is preferably 100 coulombs / cm 2 Above and 5000 Coulomb / cm 2 the following.
[0108] Even if the anode current density is less than 0.01A / cm 2 There is no particular obstacle, and it can be dealt with by extending the treatment time of the anodic polarization treatment. In addition, if the anodic current density is greater than 0.8A / cm 2 , the anodic polarization treatment can be completed in a short time. However, when a voltage rise is confirmed during the anodic polarization treatment, it is preferable to quickly stop the current supply in order to prevent the anode effect from occurring.
[0109] Furthermore, the anode current density is more preferably more than 0.05 A / cm 2 And 0.6A / cm 2 the following.
[0110] The anode current density may be a constant value, or may be gradually increased from a low value, or may be gradually decreased from a high value. The method of changing the anode current density is not particularly limited.
[0111] The amount of current per unit surface area of the anode substrate is an important value because it is related to the amount of nickel fluoride that acts as a catalyst and is deposited on the surface of the anode substrate. The amount of current per unit surface area of the anode substrate is preferably 100 coulombs / cm 2 Above, even if greater than 5000 coulomb / cm 2There is no particular problem, but the treatment time of the anodic polarization treatment becomes longer. Furthermore, the current per unit surface area of the anode substrate is more preferably 1800 coulombs / cm 2 above.
[0112] It is preferred to adjust the amount of current flowing per unit surface area of the anode substrate according to the concentration of potassium hexafluoronickel (IV)ate in the mixed solution for anode manufacturing. The amount of current flowing may be increased when the concentration of potassium hexafluoronickel (IV)ate is low, and decreased when the concentration of potassium hexafluoronickel (IV)ate is high.
[0113] The concentration of nickel electrolyte (IV) ions in the mixed solution for anode manufacturing in the anodic polarization treatment can be determined by ICP emission spectrometry. In order to free hexafluoronickel (IV) ions in the mixed solution for anode manufacturing, it is preferred that the amount of easily oxidizable impurities present in the mixed solution for anode manufacturing is small. In particular, if the amount of water in the mixed molten salt before adding potassium hexafluoronickel (IV) acid is small, the addition amount of potassium hexafluoronickel (IV) acid can be reduced, so it is preferred.
[0114] When the water in the mixed molten salt is removed by electrolysis (dehydration electrolysis), the water can be removed by electrolysis using a conductive diamond electrode, a nickel electrode, a carbon electrode, etc. When the water in the mixed molten salt is removed by electrolysis using a carbon electrode, the carbon electrode used in the dehydration electrolysis can be used as an anode substrate in the method for manufacturing an anode for fluorine gas electrolytic synthesis of the present embodiment.
[0115] In this case, a (CF)n film is formed on the surface of the carbon electrode during dehydration electrolysis, so the effect of the anodic polarization treatment in the presence of nickel hexafluoride (IV) ions is smaller than when a new carbon electrode is used, but it is not completely ineffective.
[0116] In the method for manufacturing an anode for fluorine gas electrolytic synthesis in this embodiment, a current is passed between the anode and the cathode to perform an anode polarization treatment on the anode substrate, so that nickel fluoride is attached to the surface of the anode substrate. As the nickel fluoride, a nickel fluoride having a valence greater than 2 can be cited. For example, at least one of nickel trifluoride (NiF3), nickel pentafluoride (Ni2F5) and nickel tetrafluoride (NiF4) can be cited.
[0117] Example
[0118] The present invention will be described in more detail below with reference to Examples and Comparative Examples.
[0119] [Comparative Example 1]
[0120] Use the above Figure 1A Teflon electrolytic cell was used to manufacture an anode for electrolytic synthesis of fluorine gas. KF·2HF was used as the electrolyte, and 750 g of KF·2HF was added to the main body of the electrolytic cell. The electrolyte was heated to 85°C, and the anode and cathode were immersed in it.
[0121] The cathode was a square nickel plate with a length of 5 cm and a width of 5 cm. The anode was a square diamond electrode with a length of 1 cm and a width of 1 cm, and the surface was coated with conductive diamond.
[0122] Current flows between the anode and cathode to perform dehydration electrolysis of the electrolyte. The anode current density is 0.3A / cm 2 The electrolysis time was 2 hours. The gas generated from the anode was diluted with nitrogen, and the fluorine gas was absorbed and removed by the potassium iodide aqueous solution trap. The oxygen concentration in the gas discharged from the potassium iodide aqueous solution trap was measured by gas chromatography. As a result, no oxygen was detected. It was judged that the dehydration electrolysis was completed.
[0123] Furthermore, since hydrogen fluoride in the electrolyte is consumed by dehydration electrolysis, hydrogen fluoride is intermittently supplied to the electrolyte during dehydration electrolysis to adjust the hydrogen fluoride concentration in the electrolyte to a range of 40 mass % to 43 mass %. The electrolyte prepared by such an operation is referred to as dehydrated electrolyte 1.
[0124] Next, 0.2 g of nickel fluoride was added to the dehydrated electrolyte 1 in the electrolytic cell to dissolve it. The concentration of nickel fluoride in the dehydrated electrolyte 1 was 270 mass ppm, and the amount of nickel dissolved was 160 mass ppm. The amount of nickel fluoride added was determined by measuring the amount of nickel fluoride dissolved in KF·2HF at 85°C in advance (details will be described later).
[0125] The color of the dehydrated electrolyte 1 in which nickel fluoride was dissolved was transparent. The nickel concentration in the dehydrated electrolyte 1 was also measured by ICP emission spectrometry, and the result was the same concentration as above.
[0126] A new carbon electrode was immersed in the dehydrated electrolyte 1 in which nickel fluoride was dissolved as an anode, and electrolysis was performed by passing a current of 25 mA between the anode and the cathode for 3 hours. By this electrolysis, a nickel potassium fluoride film described in Patent Document 2 was formed on the surface of the carbon electrode. The carbon electrode was a square with a length of 1 cm and a width of 1 cm. The anode current density in this electrolysis was 0.0025 A / cm 2 The current per unit surface area of the carbon electrode is 270 coulombs / cm 2 .
[0127] Here, the method for measuring the amount of nickel fluoride dissolved is described. 100 g of KF·2HF is added to a sealable Teflon container, a predetermined amount of nickel fluoride powder is added thereto, the container is sealed, and placed in a thermostatic bath at 85°C for 36 hours. However, the contents of the container are stirred from time to time. After being placed for 36 hours, the contents of the container are observed with the naked eye to confirm whether there is any dissolved residue of nickel fluoride powder.
[0128] The amount of nickel fluoride powder added was varied and the solubility was investigated. As a result, when the nickel fluoride powder was added in an amount equivalent to a concentration of 320 mass ppm or less, no dissolved residue was observed. In contrast, when a larger amount of nickel fluoride powder than the amount equivalent to a concentration of 320 mass ppm was added, dissolved residue was confirmed. After removing the dissolved residual nickel fluoride powder, the nickel concentration in KF·2HF was measured by ICP emission spectrometry, and the maximum value of the nickel concentration was 200 mass ppm.
[0129] [Comparative Example 2]
[0130] The critical current density of the anode of Comparative Example 1 was measured in the electrolyte of Comparative Example 1 by critical current density measurement method A, and the result was 0.25 A / cm 2 This critical current density is within the range of the critical current density obtained in the blank experiment, so it cannot be said that the anode effect is suppressed. In addition, from the color of the electrolyte, it cannot be said that hexafluoronickel (IV) ions are present.
[0131] [Comparative Example 3]
[0132] In Comparative Example 2, after the critical current density was measured, the anode was taken out from the electrolyte, and without water washing, it was heated to 300° C. using a high-temperature inert gas flow to volatilize the hydrogen fluoride component adsorbed on the carbon electrode. Then, energy dispersive X-ray analysis was performed using a JCM-7000 desktop scanning electron microscope manufactured by JEOL Ltd. to confirm the presence of nickel on the surface of the carbon electrode. As a result, nickel could not be confirmed because it was below the detection limit.
[0133] [Comparative Example 4]
[0134] The dehydrated electrolyte 1 obtained in the same manner as in Comparative Example 1 was placed in Figure 1 In an electrolytic cell, an anode and a cathode are immersed in the dehydrated electrolyte 1. The anode is a rectangular nickel plate with a length of 2 cm and a width of 3 cm, and the cathode is a nickel plate. Then, electrolysis is performed by passing a current of 1 A between the anode and the cathode for 26 hours, so that nickel is dissolved from the nickel plate into the dehydrated electrolyte 1.
[0135] The nickel concentration in the dehydrated electrolyte 1 was calculated to be 2800 mass ppm based on the mass reduction of the nickel plate used as the anode. However, a precipitate was generated in the dehydrated electrolyte 1. The nickel concentration in the dehydrated electrolyte 1 without the precipitate was measured by ICP emission spectrometry and the result was 270 mass ppm. The dehydrated electrolyte 1 after electrolysis was pale yellow-green.
[0136] A new carbon electrode was immersed in the dehydrated electrolyte 1 from which nickel was dissolved as an anode, and a current of 25 mA was passed between the anode and the cathode for 10 hours to perform electrolysis. By this electrolysis, a nickel potassium fluoride film described in Patent Document 2 was formed on the surface of the carbon electrode. The carbon electrode was a square with a length of 1 cm and a width of 1 cm. The anode current density in this electrolysis was 0.0025 A / cm 2 The current per unit surface area of the carbon electrode is 900 coulombs / cm 2 .
[0137] The carbon electrode with the nickel potassium fluoride film formed thereon was taken out from the dehydrated electrolyte 1, and heated to 300° C. in an inert gas without washing to volatilize the hydrogen fluoride adsorbed on the carbon electrode. Thereafter, the presence of nickel on the surface of the carbon electrode was confirmed in the same manner as in Comparative Example 3, but nickel could not be confirmed because it was below the detection limit.
[0138] [Comparative Example 5]
[0139] The dehydrated electrolyte 1 obtained in the same manner as in Comparative Example 1 was placed in Figure 1 In an electrolytic cell, nickel fluoride is added thereto and dissolved. Then, an anode is immersed in the dehydrated electrolyte 1 in which nickel fluoride is dissolved. The anode is a square carbon electrode with a length of 1 cm and a width of 1 cm. The carbon electrode is formed of highly oriented pyrolytic graphite (HOPG ZYH manufactured by Momentive Performance Materials) having a basal surface.
[0140] Then, the reference electrode was set to Ni / NiF2, and cyclic voltammetry was performed to obtain a cyclic voltammogram. The potential scanning rate was 0.4 mV / sec. The first run of the obtained cyclic voltammogram is shown in Figure 2 .Depend on Figure 2 It can be seen that the current shows a peak at a potential of about 5.5 V vs. Ni / NiF2, and the current drops sharply at a potential higher than that. This behavior is equivalent to the anode effect.
[0141] [Comparative Example 6]
[0142] The dehydrated electrolyte 1 obtained in the same manner as in Comparative Example 1 was placed in Figure 1In an electrolytic cell, lithium fluoride (LiF) powder is added thereto and dissolved. Lithium fluoride is an additive that is considered to be effective in suppressing the anode effect. The concentration of lithium fluoride in the electrolyte 1 after dehydration is 1.0 mass %.
[0143] A new carbon electrode was immersed in the dehydrated electrolyte 1 in which the lithium fluoride was dissolved as an anode, and a current of 0.05 A was passed between the anode and the cathode for 5 hours to perform electrolysis. The surface of the carbon electrode was subjected to surface treatment by the electrolysis. The carbon electrode was a square with a length of 1 cm and a width of 1 cm. The amount of current per unit surface area of the carbon electrode during the electrolysis was 900 coulombs / cm 2 Furthermore, the dehydrated electrolyte 1 during electrolysis is stirred with a stirrer so that the lithium fluoride does not settle.
[0144] After the surface treatment based on electrolysis was completed, the critical current density was measured. That is, a direct current of 25 mA was initially circulated between the anode and the cathode for 15 minutes, and then the current was increased by 25 mA every 15 minutes, and the current density before the electrolysis voltage rose sharply was taken as the critical current density. As a result, the critical current density was 0.275 A / cm 2 .
[0145] The critical current density was measured again by performing the same operation. The result showed that the critical current density was 0.30 A / cm 2 .
[0146] Based on these results, it can be seen that the anode effect cannot be suppressed by adding lithium fluoride.
[0147] [Comparative Example 7]
[0148] The dehydrated electrolyte 1 obtained in the same manner as in Comparative Example 1 was placed in Figure 1 An electrolytic cell was prepared, and a crystalline powder of potassium hexafluoronickel (IV) acid was added thereto and dissolved. The concentration of potassium hexafluoronickel (IV) acid in the dehydrated electrolyte 1 was 0.3 mass %, and the amount of nickel dissolved was 630 mass ppm. The dehydrated electrolyte 1 after the potassium hexafluoronickel (IV) acid was dissolved was red.
[0149] A new carbon electrode of 1 cm in length and 1 cm in width was immersed in a dehydrated electrolyte 1 in which potassium hexafluoronickel (IV) acid was dissolved as an anode, and a metal cathode was immersed in the electrolyte, and the electrolyte was left for 6 hours without current flowing. Then, the critical current density of the anode was measured by critical current density determination method B. As a result, the critical current density was 0.250 A / cm 2 From this result, it is understood that the effect of suppressing the anode effect cannot be obtained simply by immersing the carbon electrode in the dehydrated electrolyte 1 in which potassium hexafluoronickel (IV) oxide is dissolved.
[0150] [Example 1]
[0151] The dehydrated electrolyte 1 obtained in the same manner as in Comparative Example 1 was placed in Figure 1 An electrolytic cell was prepared, and a crystalline powder of potassium hexafluoronickel (IV) acid was added thereto and dissolved. The concentration of potassium hexafluoronickel (IV) acid in the dehydrated electrolyte 1 was 0.3 mass %, and the amount of nickel dissolved was 630 mass ppm. The dehydrated electrolyte 1 after the potassium hexafluoronickel (IV) acid was dissolved was red.
[0152] A dehydrated electrolyte 1 in which potassium hexafluoronickel (IV) acid is dissolved is used as a mixed solution for manufacturing an anode, a new carbon electrode is immersed in the mixed solution for manufacturing an anode as an anode (anode substrate), and a metal cathode is immersed. Then, electrolysis is performed by passing a current of 0.1A between the anode and the cathode for 6 hours. Through this electrolysis, nickel fluoride is formed on the surface of the carbon electrode serving as the anode substrate, and an anode for fluorine gas electrolytic synthesis is manufactured. The carbon electrode is a square with a length of 1 cm and a width of 1 cm. The anode current density in this electrolysis is 0.1A / cm 2 The current per unit surface area of the carbon electrode is 2160 coulombs / cm 2 .
[0153] The critical current density of the obtained anode for fluorine gas electrolytic synthesis was measured by critical current density measurement method A. The critical current density was 0.875 A / cm after two measurements. 2 and 0.825A / cm 2 Table 1 shows the manufacturing conditions of the anode for fluorine gas electrolytic synthesis and the measurement results of the critical current density.
[0154] [Examples 2 to 4]
[0155] An anode for fluorine gas electrolytic synthesis was produced in the same manner as in Example 1 except that the concentration of potassium hexafluoronickel (IV) oxide in the dehydrated electrolyte 1, the time of electrolysis (pretreatment), and the amount of current during electrolysis were changed as shown in Table 1.
[0156] Then, the critical current density of the obtained anode for fluorine gas electrolytic synthesis was measured by critical current density measurement method A. The measurement was performed once each. The manufacturing conditions of the anode for fluorine gas electrolytic synthesis and the measurement results of the critical current density are summarized as follows:
[0157] Table 1.
[0158]
[0159] As shown in Table 1, there is a tendency that the more the amount of potassium hexafluoronickel (IV) acid dissolved, the greater the critical current density, but at a concentration of 5000 mass ppm, the increase in critical current density is approximately saturated. In addition, as shown in the results of Examples 2 and 3, the more the amount of current during electrolysis, the more the critical current density increases, and the critical current density increases significantly compared to the blank critical current density.
[0160] [Example 5]
[0161] The anode of Example 4 for which the critical current density was measured was taken out from the mixed solution for anode production and heated to 300° C. in an inert gas to volatilize the hydrogen fluoride adsorbed on the carbon electrode. Thereafter, the presence of nickel on the surface of the carbon electrode was confirmed in the same manner as in Comparative Example 3. The presence of nickel was confirmed.
[0162] [Example 6]
[0163] The dehydrated electrolyte 1 obtained in the same manner as in Comparative Example 1 was placed in Figure 1 An electrolytic cell is prepared, and a crystalline powder of potassium hexafluoronickel (IV) acid is added thereto and dissolved. The concentration of potassium hexafluoronickel (IV) acid in the dehydrated electrolyte 1 is 0.1% by mass. Then, an anode is immersed in the dehydrated electrolyte 1 in which potassium hexafluoronickel (IV) acid is dissolved. The anode is a square carbon electrode having a length of 1 cm and a width of 1 cm. The carbon electrode is formed of highly oriented pyrolytic graphite (HOPG ZYH manufactured by Momentive Performance Materials) having a basal surface.
[0164] Then, the reference electrode was set to Ni / NiF2, and cyclic voltammetry was performed to obtain a cyclic voltammogram. The potential scanning rate was 0.4 mV / sec. The first run of the obtained cyclic voltammogram is shown in Figure 2 .Depend on Figure 2 It can be seen that the current shows a peak value at a potential of about 5.5 V vs. Ni / NiF2, and the peak current value is 2.7 times larger than the peak current value of Comparative Example 5. From this result, it can be seen that although the anode effect occurs, the current value flowing before the anode effect occurs increases by adding potassium hexafluoronickel (IV) oxide.
[0165] In addition, the results of micro-Raman spectroscopy showed that there was no difference in the peak intensity of the D band and the G band between potassium hexafluoronickel (IV) acid and nickel fluoride, so it is believed that the amount of intercalation compound inserted did not change between the two. Therefore, it is believed that the difference in the peak current value is due to the fact that the fluoride of nickel with a valence higher than divalent is used as a catalyst for the generation reaction of fluorine gas by adding potassium hexafluoronickel (IV) acid, resulting in the inhibition of the formation of a (CF)n film on the surface of the carbon electrode.
[0166] [Example 7]
[0167] An anode for fluorine gas electrolytic synthesis was produced in the same manner as in Example 4. The critical current density of the obtained anode for fluorine gas electrolytic synthesis was measured by critical current density measurement method B, and the result was 0.850 A / cm 2 .
[0168] [Example 8]
[0169] The dehydrated electrolyte 1 obtained in the same manner as in Comparative Example 1 was placed in Figure 1 An electrolytic cell was prepared, and a crystalline powder of potassium hexafluoronickel (IV) acid was added thereto and dissolved. The concentration of potassium hexafluoronickel (IV) acid in the dehydrated electrolyte 1 was 0.4 mass %, and the amount of dissolved nickel was 840 mass ppm. The dehydrated electrolyte 1 after the potassium hexafluoronickel (IV) acid was dissolved was red.
[0170] Then, a dehydrated electrolyte 1 in which potassium hexafluoronickel (IV) acid is dissolved is used as a mixed solution for manufacturing an anode, a new carbon electrode is immersed in the mixed solution for manufacturing an anode as an anode (anode substrate), and a metal cathode is immersed. Then, electrolysis is performed by passing a current of 0.3A between the anode and the cathode for 4.5 hours. Through this electrolysis, nickel fluoride is formed on the surface of the carbon electrode serving as the anode substrate, and an anode for fluorine gas electrolytic synthesis is manufactured. The carbon electrode is a square with a length of 1 cm and a width of 1 cm. The anode current density in this electrolysis is 0.3A / cm 2 The current per unit surface area of the carbon electrode is 4860 coulombs / cm 2 .
[0171] After the prepared fluorine gas electrolytic synthesis anode (the first fluorine gas electrolytic synthesis anode) was taken out from the electrolytic cell, a new carbon electrode was immersed in the dehydrated electrolyte 1 in which potassium hexafluoronickel (IV) acid was dissolved as an anode, and the same operation as above was performed to manufacture the fluorine gas electrolytic synthesis anode (the second fluorine gas electrolytic synthesis anode). The same operation was repeated to manufacture the third to sixth fluorine gas electrolytic synthesis anodes in sequence, and a total of six fluorine gas electrolytic synthesis anodes were manufactured.
[0172] After the sixth anode for fluorine gas electrolytic synthesis is taken out of the electrolytic cell, the crystalline powder of potassium hexafluoronickel (IV) acid is further added to the dehydrated electrolyte 1 and dissolved. The amount of potassium hexafluoronickel (IV) acid added is such that the concentration of potassium hexafluoronickel (IV) acid in the dehydrated electrolyte 1 increases by 0.1 mass % by addition.
[0173] A new carbon electrode was immersed in the dehydrated electrolyte 1 in which additional potassium hexafluoronickel (IV) acid was dissolved as an anode, and a current of 0.3 A was passed between the anode and the cathode for 4.5 hours to perform electrolysis. By this electrolysis, nickel fluoride was formed on the surface of the carbon electrode as the anode substrate, and the seventh anode for fluorine gas electrolytic synthesis was manufactured. The carbon electrode was a square with a length of 1 cm and a width of 1 cm. The anode current density in this electrolysis was 0.3 A / cm 2 The current per unit surface area of the carbon electrode is 4860 coulombs / cm 2 .
[0174] For the 7 fluorine gas electrolytic synthesis anodes manufactured as described above, the critical current density was measured by critical current density determination method B. The results are shown in Table 2. As can be seen from the results shown in Table 2, for the 1st to 6th fluorine gas electrolytic synthesis anodes, a tendency for the critical current density to decrease was confirmed in the order of manufacture. It is believed that this is because the nickel electrolyte of potassium hexafluoronickel (IV) acid adheres to the surface of the electrode through electrolysis, which corresponds to the situation where the concentration of hexafluoronickel (IV) ions in the electrolyte 1 gradually decreases after dehydration.
[0175]
[0176] For the seventh fluorine gas electrolytic synthesis anode, the critical current density was restored again. It is believed that by adding potassium hexafluoronickel (IV) acid again, the concentration of hexafluoronickel (IV) ions in the dehydrated electrolyte 1 increased, and the hexafluoronickel (IV) ions adhered to the surface of the carbon electrode through electrolysis.
[0177] At the time when the manufacture of the sixth fluorine gas electrolytic synthesis anode was completed, the color of the dehydrated electrolyte 1 was lighter than the initial red, but still red, so it is believed that although hexafluoronickel (IV) ions exist, their concentration has decreased. Example 8 shows that when the concentration of hexafluoronickel (IV) ions is high, more hexafluoronickel (IV) ions adhere to the surface of the carbon electrode.
[0178] Description of Reference Numerals
[0179] 10…Mixed solution for anode manufacturing
[0180] 11…Main body
[0181] 13…Next door
[0182] 21…Anode
[0183] 22…Cathode
Claims
1. A method for producing an anode for electrolytic synthesis of fluorine gas, wherein the anode can be used when electrolyzing an electrolyte containing hydrogen fluoride and a metal fluoride to electrolytically synthesize fluorine gas, the method comprising an anode polarization treatment step, In the anode polarization treatment step, an anode substrate having a carbon material is immersed as an anode, and a cathode is immersed in a mixed solution for anode manufacturing containing hydrogen fluoride, metal fluoride and potassium hexafluoronickel (IV) oxide, and an electric current is passed between the anode and the cathode to perform an anode polarization treatment on the anode substrate, thereby attaching nickel fluoride to the surface of the anode substrate. 2 . The method for producing an anode for fluorine gas electrolytic synthesis according to claim 1 , wherein the concentration of the potassium hexafluoronickel(IV)ate in the mixed solution for producing the anode is 500 ppm by mass or more and 5000 ppm by mass or less.
3. The method for manufacturing an anode for fluorine gas electrolytic synthesis according to claim 1 or 2, wherein in the anode polarization treatment, the anode current density is 0.01 A / cm 2 Above and 0.8A / cm 2 The current per unit surface area of the anode substrate is 100 coulombs / cm 2 Above and 5000 Coulomb / cm 2 the following. 4 . The method for producing an anode for fluorine gas electrolytic synthesis according to claim 1 , wherein the nickel fluoride has nickel ions having a valence greater than 2. 5 . The method for producing an anode for fluorine gas electrolytic synthesis according to claim 1 , wherein the nickel fluoride is at least one of nickel trifluoride, nickel pentafluoride and nickel tetrafluoride. 6 . The method for producing an anode for fluorine gas electrolytic synthesis according to claim 1 , wherein the metal fluoride is at least one of potassium fluoride and cesium fluoride. 7 . The method for producing an anode for fluorine gas electrolytic synthesis according to claim 1 , wherein the ratio of the molar amount of the hydrogen fluoride contained in the mixed solution for producing the anode to the molar amount of the metal fluoride is 1.6 or more and 3.2 or less.
8. The method for producing an anode for fluorine gas electrolytic synthesis according to claim 1 or 2, wherein the cathode is an electrode formed of at least one of iron, nickel, copper and a copper-nickel alloy.
